2022
DOI: 10.1186/s12962-022-00338-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in productivity in healthcare services in the Kingdom of Saudi Arabia

Abstract: Background Amid the rising demand for healthcare services in Saudi Arabia, there is a need to monitor, evaluate, and improve performance in the delivery of these services. In this regard, the aim of this study was to estimate changes in total factor productivity (TFP) in healthcare services across the health system administrative regions in Saudi Arabia from 2006 to 2018. The contributions of changes in efficiency and technology to the observed changes in TFP were further evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The results indicated that, on average, TFPC, TEC, and TC of all 31 provinces showed a slight decline in 10 years. Al-Hanawi and Makuta 47 also indicated TFP for healthcare services has decreased on average by 5.6% per year primarily due to a technical regression from 2006 to 2018. Base on the overall situation of each province, the decline in total factor productivity may be mainly attributed to changes in technical efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that, on average, TFPC, TEC, and TC of all 31 provinces showed a slight decline in 10 years. Al-Hanawi and Makuta 47 also indicated TFP for healthcare services has decreased on average by 5.6% per year primarily due to a technical regression from 2006 to 2018. Base on the overall situation of each province, the decline in total factor productivity may be mainly attributed to changes in technical efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The first one uses Shannon entropy to integrate the different DEA model measurements [ 37 , 38 ]. The second one obtains the CES by evaluating the importance of each combination of variables to improve the DEA identification and provides a complete ranking [ 11 , 39 ]. In this paper, the original ranking combination is improved somewhat by taking into account the undesirable output indicators based on the study conducted by Xie [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…In terms of the efficiency measurement of healthcare institutions, Sherman [ 37 ] was the first to use the DEA method, and afterwards, numerous scholars enriched this field of research [ 38 , 39 , 40 , 41 ]. In particular, the DEA method has also made great progress in evaluating the efficiency of Chinese healthcare organizations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the BCC model established by [12] under the assumption of variable returns to scale (VRS) has been utilized frequently. The selection of the CCR or BCC model depends on the context of the examined problem (i.e., the technology linking the inputs and outputs in the transformation process) [13].…”
Section: Evaluating Efficiency In Healthcarementioning
confidence: 99%